THE USE OF SIMULATION AND ANIMATION OF VIRTUAL LABORATORY-BASED PRACTICAL LEARNING FOR SCIENCE TEACHER GROUPS - Syamsuriana Basri; Sri Maya; Irsan Irsan (JCES (Journal of Character Education Society), 2021)
Abstrak: Pelatihan  ini memiliki tujuan memberikan pengetahuan dan keterampilan terkait 1) Penjelasan Pemanfaatan Teknologi dalam Pembelajaran Praktikum IPA, 2) pelatihan Pembuatan Media Pembelajaran Praktikum Berbasis Simulasi dan Animasi. Dan 3) pelatihan Pembuatan Chanel Youtube.   Peserta dalam pelatihan ini adalah guru IPA SMP yang tergabung dalam MGMP IPA Kabupaten Pangkajene dan Kepulauan sejumlah 15 orang guru. Metode yang digunakan presentasi, demonstrasi kemudian  praktik serta metode yang digunakan untuk mengukur peningkatan pemahaman yakni menyebarkan kuesioner dengan menggunakan skala interval kemudian data dianalisis melalui microsoft exel untuk mencari rata-rata dan persentasi setiap indikator dan aspek yang diamati. Hasil dari pelatihan yang diperoleh yaitu 1) peningkatan Pemahaman Pemanfaatan Teknologi dalam Pembelajaran Praktikum IPA sebesar 35,44%, 2) peningkatan pengetahuan dan keterampilan Pembuatan Media Pembelajaran Praktikum Berbasis Simulasi dan Animasi sebesar 71,19%, dan 3) peningkatan pengetahuan dan keterampilan Pembuatan Chanel Youtube sebesar 74,32%. Hal dari kegiatan ini mendapatkan pengetahuan dan keterampilan terkait media serta pembuatannya yang dapat digunakan dalam pembelajaran praktikum secara virtual, khususnya mata pelajaran IPA.Abstract: This training has the aim of providing knowledge and skills related to 1) Explanation of the Use of Technology in Science Practicum Learning, 2) Training on Making Practical Learning Media Based on Simulation and Animation. And 3) Youtube Chanel Creation training. Participants in this training are science teachers for junior high schools who are members of the MGMP for science in Pangkajene and Islands Regency, with a total of 15 teachers. The method used is presentation, demonstration, then practice and the method used to measure the increase in understanding is distributing questionnaires using an interval scale then the data is analyzed through Microsoft Excel to find the average and percentage of each indicator and aspect observed. The results of the training obtained are 1) an increase in understanding of the use of technology in science practicum learning by 35.44%, 2) an increase in knowledge and skills in making simulation and animation-based practical learning media by 71.19%, and 3) an increase in knowledge and skills in making Youtube Chanel by 74.32%. The thing from this activity is getting knowledge and skills related to media and their manufacture that can be used in virtual practicum learning, especially science subjects.